Convergent reductions in interhemispheric functional, structural and callosal connectivity in Parkinson’s disease - Erlei Wang; Yujing Jia; Luqi Cheng; Chengjie Mao; Yiqing Bao; Junkang Shen; Yuanchao Zhang; Yuanchao Zhang; Guohua Fan (Frontiers in Aging Neuroscience)
BackgroundAbnormal interhemispheric functional connectivity is frequently reported in Parkinson’s disease (PD), but its structural basis remains unclear. This study aimed to investigate changes in interhemispheric functional, structural, and callosal connectivity, as well as their interrelationships, in PD patients.MethodsThe study included 57 PD patients and 50 healthy controls (HCs). Interhemispheric functional connectivity was evaluated using voxel mirrored homotopic connectivity (VMHC) derived from resting-state functional MRI, while structural connectivity was measured through homotopic cortical thickness covariance from T1-weighted MRI. The corpus callosum (CC), connecting bilateral regions with VMHC differences, was assessed using fractional anisotropy (FA) from diffusion MRI. Pearson’s correlation was used to evaluate the interrelationships among imaging data and their clinical relevance.ResultsCompared to HCs, PD patients showed reduced VMHC and interhemispheric structural connectivity in similar brain regions, displaying a positive correlation trend between these measures. The affected regions encompassed the bilateral sensorimotor cortices (precentral gyrus, postcentral gyrus, and paracentral lobule) and posterior cortical areas, including the superior parietal lobule, supramarginal gyrus, precuneus, middle occipital gyrus, fusiform gyrus, as well as the superior and middle temporal gyri. FA in the CC, connecting regions with reduced VMHC, was also lower in PD patients. Additionally, interhemispheric structural, functional, and callosal connectivity reductions were, respectively, related to cognitive impairment, motor dysfunctions, and disease duration in PD.ConclusionThe study identified convergent reductions in interhemispheric functional, structural and callosal connectivity in PD patients, emphasizing the strong link between structural and functional brain abnormalities. Our findings may provide new insights into the pathophysiology of PD.